Solar Panel Implementation for Household Electricity in Indonesia: Environmental and Economic Implications: Penerapan Panel Surya untuk Listrik Rumah Tangga di Indonesia: Implikasinya terhadap Lingkungan dan Ekonomi - Nico Cahya Pradana Pradana; Muhammad Alvan Rizki; Atik Wahyuni; Budwi Harsono (Academia Open, 2023)
This study explores the potential of solar energy as a sustainable alternative to coal-based electricity generation in Indonesia, aiming to address environmental concerns. It assesses the feasibility of household-level solar panel adoption for reducing electricity costs and enhancing energy self-sufficiency. Using photovoltaic technology, the research examines solar energy conversion and battery storage, focusing on optimal daylight utilization. Findings reveal substantial cost-saving prospects for households and stress the environmental benefits of decreasing reliance on conventional electricity sources. The study highlights the significance of public awareness and government support for solar panel adoption, emphasizing its role in economic stability and resource allocation to productive sectors. It advocates for empowering and educating the public about solar panel usage, which not only lowers electricity expenses but also promotes economic stability by reallocating funds to other industries, thus contributing to Indonesia's economic well-being and sustainable energy future. Highlights : This study evaluates solar energy's potential as a sustainable alternative to coal-based electricity in Indonesia, addressing environmental concerns. It emphasizes the feasibility of household-level solar panel adoption for cost reduction and energy self-sufficiency, focusing on photovoltaic technology and optimal daylight utilization. The research underscores the importance of public awareness and government support for solar panel adoption, highlighting its role in economic stability and resource allocation to productive sectors, ultimately contributing to a sustainable energy future. Keywords: Solar Energy, Sustainability, Household Adoption, Photovoltaic Technology, Environmental Benefits